On-demand QoS multicast routing for mobile ad hoc networks - Teo, Hui Seong. (2008)
The main objectives of this research project is to propose a new on-demand QoS Multicast for MANETs for real-time multimedia data delivery and to implement the proposed algorithm for comparison between the best effort mode and the proposed bandwidth reservation mode.